Smart Nanocarrier Based on PEGylated Hyaluronic Acid for Cancer Therapy - Choi, Ki Young; Yoon, Hong Yeol; Kim, Jong-Ho; Bae, Sang Mun; Park, Rang-Woon; Kang, Young Mo; Kim, In-San; Kwon, Ick Chan; Choi, Kuiwon; Jeong, Seo Young; Kim, Kwangmeyung; Park, Jae Hyung (AMER CHEMICAL SOC, 2011)
Tumor targetability and site-specific drug release of therapeutic nanoparticles are key factors for effective cancer therapy. In this study, poly(ethylene glycol) (PEG)-conjugated hyaluronic acid nanoparticles (P-HA-NPs) were Investigated as carriers for anticancer drugs including doxorubicin and camptothecin (CPT). P-HA-NPs were internalized into cancer cells (SCC7 and MDA-MB-231) via receptor-mediated endocytosis, but were rarely taken up by normal fibroblasts (NIH-3T3). During in vitro drug release tests, P-HA-NPs rapidly released drugs when incubated with cancer cells, extracts of tumor tissues, or the enzyme Hyal-1, which is abundant In the intracellular compartments of cancer cells. CPT-loaded P-HA-NPs (CPT-P-HA-NPs) showed dose-dependent cytotoxicity to cancer cells (MDA-MB-231, SCC7, and 116) and significantly lower cytotoxicity against normal fibroblasts (NIH-3T3) than free CPT. Unexpectedly, high concentrations of CPT-P-HA-NPs demonstrated greater cytotoxicity to cancer cells than free CPT. An in vivo biodistribution study Indicated that P-HA-NPs selectively accumulated into tumor sites after systemic administration into tumor-bearing mice, primarily due to prolonged circulation In the blood and binding to a receptor (CD44) that was overexpressed on the cancer cells. In addition, when CPT-P-HA-NPs were systemically administrated into tumor-bearing mice, we saw no significant increases in tumor size for at least 35 days, implying high antitumor activity. Overall, P-HA-NPs showed promising potential as a drug carrier for cancer therapy.
Keywords: INTRACELLULAR DRUG-DELIVERY; BLOCK-COPOLYMER MICELLES; ANTITUMOR EFFICACY; PROSTATE-CANCER; TUMOR-CELLS; PH; NANOTECHNOLOGY; EXPRESSION; POLYMER; CD44